Studi Pustaka: Ekstraksi Pewarna Alami dari Tanaman di Indonesia - Yuyun Yuniati; Kejora Handarini; Retnani Rahmiati (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Dyes have played an important role in human life, therefore the production of dyes has continued to increase from the past until now. The use of synthetic chemical dyes has apparently caused various health and environmental problems, this is what has triggered the return to use of natural dyes. Through advances in science and technology, research related to the extraction of natural dyes in Indonesia was carried out until 31 scientific reports were found that studied this matter in the last ten years. Literature studies with secondary data have summarized the novelty of research related to the extraction of natural dyes from plants, where currently flower objects are of great interest for observational studies. Various types of flowers have potential pigments that can be converted into natural dyes. The maceration extraction method is still the choice for extracting plant bioactive substances. Recently a study on the extraction of dyes from fruit peel waste was also carried out. It is hoped that the development of information related to the extraction of natural dyes will have more opportunities to be applied in various aspects.